The Impact of Capital Structure on Financial Performance of Manufacturing Firms: Evidence from US - Abu Arrah, Hamza (My University, 2024)
This paper investigates the impact of leverage on manufacturing firms’ performance measured by Return on Assets (ROA) for the primary test and Tobin’s Q for the robustness test. Also, the paper investigates whether leverage level has a varying impact on the performance of firms during recessions, compared to the performance during ordinary economic periods. Furthermore, the study examines whether higher or lower debt levels can optimize the performance of highly and conservatively levered firms. Leverage is measured as the ratio of Total Debt to Total Assets. Financial performance is measured with Return on Assets (ROA) for primary tests and Tobin’s Q for robustness. The study employs a panel data regression of 641 manufacturing firms in the US market over 21 years (2003-2023). Empirical findings reveal that debt levels have a significant negative impact on firms’ performance using ROA. The results are robust when substituting ROA with Tobin’s Q. However, during recessions, the analysis does not show a significant impact of recession on firms’ performance. Additionally, the results do not provide significant evidence that highly and conservatively levered firms perform differently during recessions. Moreover, less debt for conservatively levered firms significantly optimizes financial performance. On the other hand, the results do not provide significant evidence of whether highly levered firms can optimize their performance by increasing or decreasing the debt levels in their capital structure. Finally, even though the leverage negatively impacts firms’ performance, the comparative analysis between highly and conservatively levered sub-samples showed that highly levered firms perform better. That implies the non-linearity of the relationship and reinforces the urge to investigate the relationship among segregated sub-samples of firms based on relevant characteristics, such as firm size, asset structure, liquidity, and industry and sector
Keywords: finance; profitability; capital; recession; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance